Contribution of Arm Muscle Strength, Leg Muscle Endurance, and Eye Coordination To Volley Ball Underhand Pass Ability - Sahabuddin, Sahabuddin; Hakim, Hikmad; Muslim, Muslim (Journal Coaching Education Sports, 2021)
This study aims to determine the contribution of arm muscle strength, leg muscle endurance, and eye-hand coordination to the ability to underhand pass in volleyball. This research belongs to the type of descriptive research. The population of this study was all male students of SMK Negeri 2 Watangsoppeng, Soppeng Regency with a total sample of 40 people selected by random sampling. The data analysis technique used is the correlation analysis technique using the SPSS Version 22.00 system at a significant level of 95% or 0.05. Based on the results of data analysis, this study concludes that: (1) Arm muscle strength has a contribution to the ability of underhand pass in volleyball games in students of SMK Negeri 2 Watang Soppeng, Soppeng Regency by 53.8%; (2) Leg muscle endurance has a contribution to the ability to underhand pass in volleyball in SMK Negeri 2 Watang Soppeng students, Soppeng Regency by 80.9%; (3) Eye-hand coordination has a contribution to the ability of underhand pass in the volleyball game in students of SMK Negeri 2 Watang Soppeng, Soppeng Regency by 52.1%; and (4) arm muscle strength, leg muscle endurance and eye-hand coordination have a contribution to the ability of underhand pass in volleyball games in students of SMK Negeri 2 Watang Soppeng, Soppeng Regency by 81.6%.